DESENVOLVIMENTO DE CIMENTOS ÁLCALI ATIVADOS COMPOSTOS COM RESÍDUOS DE MINERAÇÃO DE CARVÃO - Frasson, Bruna Juvêncio; Rocha, Janaíde Cavalcante (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Wastes from coal washing has potential for being use as building materials, from pozzolanic materials to aluminosilicate sources in alkali-activated cements. The aim of this work was to evaluate the use of pre-treated mining residues (RCE and LMDT) in alkali-activated cements by analyzing the performance of different types of alkaline solutions and mechanical behavior of pastes. The results showed that the optimized alkali solutions was the composition of Na2SiO3 + NaOH (solid), because wasn`t appearance of efflorescence and had tendency to hardening. With that definition was mixed pastes to compressive strength test, the results showed low value for AARCE (1.83 MPa) in 24 hours and increase of strength for AALMDT (13.91 MPa). This research demonstrated the potential of using waste from coal mining, mitigating the environmental impacts.